Good peers, good apples? Peer effects in portfolio quality - Olga Balakina; Claes Bäckman; Andreas Hackethal; Tobin Hanspal; Dominique Marcel Lammer (Leibniz Institute for Financial Research SAFE, 2022)
Peer effects can lead to better financial outcomes or help propagate financial mistakes across social networks. Using unique data on peer relationships and portfolio composition, we show considerable overlap in investment portfolios when an investor recommends their brokerage to a peer. We argue that this is strong evidence of peer effects and show that peer effects lead to better portfolio quality. Peers become more likely to invest in funds when their recommenders also invest, improving portfolio diversification compared to the average investor and various placebo counterfactuals. Our evidence suggests that social networks can provide good advice in settings where individuals are personally connected.
Keywords: D14; G11; G4; 330; Household finance; investment decisions; investment behavior; peer effects; social networks